Family Communication Model on Preserving Romance for Elderly Spouse - Supratman, Lucy Pujasari; Wahyudin, Aep (Jurnal Komunikasi, 2023)
Every married couple would want to have a golden marriage that lasts happily ever after. There were 15 elderly couples who had entered a golden marriage being interviewed. This research was conducted at 2 regions (Bandung and Subang) in West Java. We used qualitative method with phenomenology approach.  Data collecting was done through interview and observation.  The results found that these elderly couples communicate in different ways to maintain their romances.  They keep on their commitment in supporting the couple hobbies, being honest, doing nonverbal communication of romantic movement/gestures, saying thanks, and giving forgiveness sincerely. The model proposed on this research findings are being commitment, forgiveness, honesty, thanking, romance action and marriage as worship. These communication model that the elderly spouses applied in their daily life doesn’t seem smooth as it is.  They always give the opportunity of each other to improve themselves better for the sake of long-lasting marriage.  These elderly couples realized about their imperfectness and keep learning all the time to be mature couple.  As they have matured mind, every barrier in the marriage will always solve wisely and happily by the couple. These family communication pattern have finally formed the long lasting marital harmony of romantic relationship between the elderly couple to create honor and trust.